2015
DOI: 10.14712/23362936.2015.48
|View full text |Cite
|
Sign up to set email alerts
|

Isoelectric Focusing of Serum Apolipoprotein C-III as a Sensitive Screening Method for the Detection of O-glycosylation Disturbances

Abstract: Apolipoprotein C-III (ApoC-III) is a glycoprotein carrying the most common O-linked glycan structure and is abundantly present in serum, what renders it a suitable marker for analysis of O-glycosylation abnormalities. Isoelectric focusing followed by a Western blot of ApoC-III, using PhastSystem™ Electrophoresis System (GE Healthcare), was introduced as a rather simple and rapid method for screening of certain subtypes of inherited glycosylation disorders. The study's aim was to establish this method in our la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…In healthy adults, MALDI‐MS revealed, in terms of relative peak areas, increased levels of apoC‐III 0a (aglycosylated species) and decrease of apoC‐III 2 when compared with pediatric samples (our data; not shown). These findings are in agreement with a recent paper reporting age‐dependent apoC‐III sialylation by IEF . Therefore, we compared the results of apoC‐III glycosylation analysis of our COG5‐CDG patients with those of age‐matched healthy pediatric controls.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…In healthy adults, MALDI‐MS revealed, in terms of relative peak areas, increased levels of apoC‐III 0a (aglycosylated species) and decrease of apoC‐III 2 when compared with pediatric samples (our data; not shown). These findings are in agreement with a recent paper reporting age‐dependent apoC‐III sialylation by IEF . Therefore, we compared the results of apoC‐III glycosylation analysis of our COG5‐CDG patients with those of age‐matched healthy pediatric controls.…”
Section: Resultssupporting
confidence: 65%
“…These findings are in agreement with a recent paper reporting age-dependent apoC-III sialylation by IEF. [23] Therefore, we compared the results of apoC-III glycosylation analysis of our COG5-CDG patients with those of age-matched healthy pediatric controls. Figure 1 shows representative MALDI mass spectra of apoC-III glycosylation profiles of a control and a patient, respectively.…”
Section: Maldi-tof Ms Analysis Of Serum Apoc-iii From Controls and Comentioning
confidence: 99%
“…The apoCIII‐0a/apoCIII‐1 ratio differed significantly between the under 1 year and older age groups ( p < 0.0001, Welch's t test) (Figure 4). This result indicated that occupancy of the glycosylation site by GalNAc was high in early infancy, an observation consistent with the report of Ondrušková et al who analyzed 170 healthy individuals (age range: 1 day to 42 years) employing isoelectric focusing and found a relative rise in apoCIII‐0 with increasing age 23 . The attachment of GalNAc is probably dependent on various factors including the enzymatic activity of transferring GalNAc to apoCIII, the supply of donor sugar‐nucleotide Uridine diphosphate (UDP)‐GalNAc, the rate of production and clearance of apoCIII protein and so on.…”
Section: Resultssupporting
confidence: 90%
“…This result indicated that occupancy of the glycosylation site by GalNAc was high in early infancy, an observation consistent with the report of Ondrušková et al who analyzed 170 healthy individuals (age range: 1 day to 42 years) employing isoelectric focusing and found a relative rise in apoCIII-0 with increasing age. 23 The attachment of GalNAc is probably dependent on various factors including the enzymatic activity of transferring GalNAc to apoCIII, the supply of donor sugar-nucleotide Uridine diphosphate (UDP)-GalNAc, the rate of production and clearance of F I G U R E 2 Matrix-assisted laser desorption/ionization (MALDI) mass spectrometry (MS) profiling of apoCIII glycoforms. The mucin-type core-1 glycoforms corresponding to apoCIII ions and the synthetic pathway are illustrated above the mass spectrum.…”
Section: Age Dependencymentioning
confidence: 99%
See 1 more Smart Citation